DEVELOPMENT OF A MOBILE APPLICATION FOR LEARNING THE KAZAKH LANGUAGE - Kozhakhmet С.Қ.; Е.П.; Dalbekova Қ.С; А.К. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
During the research, a mobile educational application was developed. Using a mobile app is a key tool for improving user knowledge. The app helps users to study without a teacher in their free time. The app was built using the Xcode IDE. The optional quiz includes many features such as reading, grammar, verbs, and speaking. This will be of great help for users who want to learn more Kazakh. The Kazakh language is developing rapidly. Therefore, the pace of learning the Kazakh language is growing day by day. Currently, it is beneficial to use mobile applications related to distance learning. The application helps to learn the Kazakh language anytime, anywhere. The grammar of the Kazakh language is more complex than other languages. With this in mind, each section of the appendix describes the rules of 1-2 grammars. At the end of each section there is a set of dictionaries to speed up the construction of user sentences. That is, the user who has passed all the sections speaks the Kazakh language at a high level.